microRNA, the Innate-Immune System and SARS-CoV-2 - Hill, James M.; Lukiw, Walter J. (Frontiers in Cellular and Infection Microbiology, 2022)
The single-stranded viral RNA (ssvRNA) known as the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes COVID-19 can be effectively inactivated by a number of natural ribonucleic acid-based host cell defenses. One of the most important of these defenses includes the actions of a class of small non-coding RNAs (sncRNAs) known as microRNAs (miRNAs). Via base-pair complementarity miRNAs are capable of specifically targeting ssvRNA sequences such as SARS-CoV-2 promoting its inactivation and neutralization. RNA-sequencing and bioinformatics analysis indicate that multiple naturally-occurring human miRNAs have extensive complementarity to the SARS-CoV-2 ssvRNA genome. Since miRNA abundance, speciation, and complexity vary significantly amongst human individuals, this may in part explain the variability in the innate-immune and pathophysiological response of different individuals to SARS-CoV-2 and overall susceptibility to ssvRNA-mediated viral infection.